(untitled) (Revista de Ciências Agroveterinárias, 2018)
This study evaluated the hydrolytic and phosphate-solubilizing potentials of soil bacteria isolated from a red latosol (oxisol) under maize cultivation. Rhizosphere soil (SR) and non-rhizosphere soil (NR) were collected and, subsequently, distinct bacterial colonies were isolated in pure cultures. Solid culture media were employed to evaluate production of hydrolases and phosphate solubilization by the isolates. From SR and NR, 30 and 19 distinct colonial types were isolated, respectively. From 29 SR isolates, 68.9%, 65.5%, 20.7% and 24.1% displayed proteolytic, cellulolytic, amylolytic, and phosphate-solubilizing activities, respectively. From the NR isolates, 57.9% produced cellulase, 42.1% protease, 57.9% amylase and 21.0% solubilized phosphate; however, 31.6% of these isolates did not display any activity. Diverse bacteria presented combined activities, representing about 58% of the SR and NR isolates. In addition to environmental and agricultural relevance, the microbial ability to secrete enzymes related to carbon and nitrogen cycles and phosphate solubilization might be important from a biotechnological perspective.